HATRED OF/AND DEMOCRACY: THE POLITICAL CONTRADICTIONS OF REDDIT’S MODERATION STRUCTURE - Smith, Trevor Garrison (AoIR Selected Papers of Internet Research, 2018)
This paper seeks to interpret Reddit moderation as a problem of political theory, rather than as a debate between the merits of human moderation and algorithmic moderation. Analyzing Reddit’s moderation structure shows that both the human moderation and the algorithmic moderation reinforce a form of anti-politics which leaves users feeling like they have no input and thus no interest in the well-being of the subreddits in which they participate. Online governance structures are largely top down and authoritarian in nature, despite often being couched in democratic rhetoric, reflecting what Jacques Rancière describes as a hatred of democracy. By looking at the example of how r/Canada came to be widely disparaged on Reddit as a bastion of hate, I make the argument that the key to rooting out online hate is not through more human moderation or by giving algorithms more control, but by creating a democratic culture of buy-in through which users are empowered with responsibility for the quality of content in a discussion space.